Effect of land use on water yield from small agricultural watersheds of western ghats - ABDUL HAKKIM V.M; Er. Xavier K. Jacob (Guide) (Tavanur 1993 Kelappaji College of Agricultural Engineering and Technology)
Effect of land use on water yield from small agricultural watersheds of western ghats
Effect of land use on water yield from small agricultural watersheds of western ghats